An Exploratory Study on Parental Attachment and Juvenile Delinquency - Ismail, Ismadi (Universiti Sains Malaysia, 2006)
The present study was designed to investigate the relationship between parental attachment and delinquency among juveniles with parental history of incarceration and juveniles without parental history of incarceration. A sample of 172 juveniles were rendamly selected by prison officer from two different Youth Rehibilitation Center. The respondents consist of 141 male juveniles at Sekolah Henry Gurney, Teluk Emas, Melaka and 31 female juveniles from Sekolah Henry Gurney, Batu Gajah, Perak. A set of questionnaire was used to measure parental attachment quality and delinquency among juveniles. The parental attachment questionnaire comprised 27 items divided into three main subscales, i.e. trust, communication, and alienation. In addition, the questionnaire on selfreported delinquency comprised 29 items. The results were tested by the Pearson product moment correlation and t-test analysis using SPSS/PC + package for statistical analysis. The result indicated no significant correlation between parental attachment and delinquency among both male and female juveniles. The t-test analysis indicated no significant differences in delinquency as well as parental attachment between the juveniles with parental history of incarceration and without parental history of incarceration. The result also showed a significant difference between gender and delinquency.